Study on Self Compacting Concrete with Polypropylene Fibers and Ground Granulated Blast Furnace Slag - Deepak G. Appaji, Chethan K. (International Journal of Advanced Science and Technology, 2020)
Self Compacting concrete adopted in various applications. Addition of fibers to SCC has been improved strength and durability of concrete. The study presents an investigation on compressive strength in polypropylene fiber reinforced SCC. Six mixes of concrete with varying percentage of fibers (1% and 2%) are considered. Strength Mix-S (100% Cement) has shown more strength when compared to Mix-S1(100% cement with 1%PPF) & Mix-S2(100% cement with 2%PPF) and Mix-SG (70% cement + 30% GGBS) shows greater strength when compared to all other mixes to Mix-SG1(70% cement + 30% GGBS with 1%PPF) & Mix-SG2(70% cement + 30% GGBS with 2%PPF).